Implementasi Kurikulum Al-Islam dan Kemuhammadiyahan dalam Meningkatkan Sikap Religiusitas Mahasiswa di Universitas Muhammadiyah Sumatera Utara - Nur Rahmah Amini; Nadlrah Naimi; Said Ahmad Sarhan Lubis (UMSU, 2019)
Muhammadiyah University of North Sumatra (UMSU) is the Best Private University in North Sumatra. From innovative and innovative education and learning programs, finally students can become competent, intelligent and trustworthy and have exceptional competitiveness at both National and International levels. In realizing maximum education, especially in the formation of student religiosity attitudes that are in accordance with the values of Al-Islam and Kemuhammadiyahan, the Muhammadiyah University of North Sumatra (UMSU) in collaboration with the Al-Islam Agency and kemuhammadiyahan (BIM) formed Al-Islam learning curriculum and Kemuhammadiyahan is in accordance with the guidance of the Muhammadiyah tarjih. As lecturers in Al-Islam and Kemuhammadiyahan courses, we must have targets in learning, for example various innovations that we need to implement in learning activities so that students can have a religious attitude and can understand the values of Al-Islam and Kemuhammadiyahan well and practice in everyday life. This study aims to find out the extent of the role of Al-Islam Kemuhammadiyahan subjects in developing the attitude of religiosity of students at Muhammadiyah University in North Sumatra. This study uses mixed method with analytical descriptive style with IPO approach (Inputs, Processes and Products), because there are differences in religious understanding from respondents in different situations